Дослідження механізму ферментативного гліцеролізу жирів - Некрасов, Павло Олександрович (НТУ "ХПІ", 2009)
In presented work it was ascertained that enzymecatalyzed glycerolysis of fats obeys ping-pong bi-bi mechanism. According to the mechanism scheme the glycerolysis is the complex process which involves three competitive reactions. Computed equilibrium constants gave an opportunity to establish the dominant reaction.
Keywords: пальмова олія; моноацилгліцерини